2017
DOI: 10.5194/acp-17-14811-2017
|View full text |Cite
|
Sign up to set email alerts
|

Retrieving characteristics of inertia gravity wave parameters with least uncertainties using the hodograph method

Abstract: Abstract. We have analyzed wind velocities measured with high-resolution Global Positioning System (GPS) radiosondes which have been flown continuously from Hyderabad for 120 h with an interval of 6 h. Hodograph method has been used to retrieve inertia gravity waves (IGWs) parameters. Background winds are removed from the time series by detrending, whereas polynomials of different orders are removed to obtain the fluctuations from individual profiles. A Butterworth filter is used to extract the monochromatic I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The bispectral analysis is helpful to explain nonlinear resonant wave-wave interactions (Wüst and Bittner, 2006). The rotary spectral technique (Vincent, 1984) or Hodograph analysis (Hirota and Niki, 1985) is popular to characterize the inertia gravity wave intrinsic frequency and propagation direction, though it demands the presence of a single coherent wave source and does not yield good results at the mixture of different frequencies present in the perturbation profiles (Dutta et al, 2017). In general, in a plot of fluctuation components of winds, an ellipse would be fit and the rotational direction of the ellipse would decide the propagation direction of waves.…”
Section: Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bispectral analysis is helpful to explain nonlinear resonant wave-wave interactions (Wüst and Bittner, 2006). The rotary spectral technique (Vincent, 1984) or Hodograph analysis (Hirota and Niki, 1985) is popular to characterize the inertia gravity wave intrinsic frequency and propagation direction, though it demands the presence of a single coherent wave source and does not yield good results at the mixture of different frequencies present in the perturbation profiles (Dutta et al, 2017). In general, in a plot of fluctuation components of winds, an ellipse would be fit and the rotational direction of the ellipse would decide the propagation direction of waves.…”
Section: Other Methodsmentioning
confidence: 99%
“…The difference between soundings and the background profiles defines the wave field which can be filtered out by using a Fourier transform to remove the very high or very low frequency oscillations. Dutta et al (2017) reported the use of different order polynomial fits (2-9) as the background on observed instantaneous wind profiles by global positioning system radiosondes over Hyderabad (17.4 °N, 78.5 °E). They observed the difference of wave parameters calculated by varying order of polynomials, and found reasonably reduced difference when a "Butterworth" filter was applied to extract inertia gravity wave components.…”
Section: Polynomial Fitmentioning
confidence: 99%
“…The hodograph analysis is obtained from the perturbation components of zonal ( u ′) and meridional wind ( v ′) of the ECMWF 91 model level data over Kolkata to estimate the energy propagation direction with a uncertainty of 180° (Vincent & Joan Alexander, ). To reduce the uncertainty the temperature perturbation has been plotted with the in‐phase velocity (Dutta et al, ). In‐phase wind is U cos ѳ, where U is the total wind and ѳ is the orientation angle of the u ′ v ′ hodograph.…”
Section: Methodsmentioning
confidence: 99%
“…In‐phase wind is U cos ѳ, where U is the total wind and ѳ is the orientation angle of the u ′ v ′ hodograph. The clockwise rotation of in‐phase wind and temperature perturbation hodograph indicates horizontal wave propagation along the orientation angle of u ′ v ′ hodograph (Dutta et al, ). Counterclockwise rotation indicates the propagation direction in the opposite direction (Dutta et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The model basically calculates the phase velocity and amplitude of the wave generated from a thunderstorm. The individual vertical profiles of radiosonde can be used to determine the perturbation in the horizontal wind profiles and also the power spectrum of the signal [76], [82]. The power spectrum is analysed for significant waves based on the red-noise spectrum, and the most dominant frequency is used for the conclusion here.…”
Section: Validationmentioning
confidence: 99%